Methodology for the analysis of presidential discourses as mediators narrations - Gómez Villanueva, Beatriz (Mediaciones Sociales, 2016)
The object of the present paper is the methodological approach offered by the social mediation for the analysis of political discourses. The representations generated by Mexican governments in their discourses, for their performance accountability, are considered from the point of view of the cognitive mediation, in order to understand how the events are interpreted and how they are communicated. So we resort to study government referents even though the construction of collective representations is determined by many factors. Their value lies on the fact that the exercise of power in Mexico is based on the imagery of the uninterrupted Revolution, which gave legitimacy to the single party system that ruled in the country for more than 70 year. Besides, this paper offers an annex which displays a thorough review of studies dealing with communicative mediations.
Keywords: presidential discourses; communicative mediation; principles; themes; situations.